(untitled) (Acta Scientiarum. Agronomy, 2025)
Uniform seed distribution and an optimal plant stand are crucial for maximizing soybean yield. Additionally, a robust root system is essential for effective water and nutrient absorption through biological nitrogen fixation. This study investigated the impact of planting speed and coinoculation (Bradyrhizobium japonicum + Azospirillum brasilense) on plant distribution, nodulation, and soybean grain yield. Six field experiments were conducted during the 2018/19 and 2019/20 crop years in Santa Maria (two planting seasons per year) and Restinga Sêca, Brazil. The experiments utilized a randomized block design with four replications and treatments arranged in a 2 x 5 factorial design, assessing coinoculation (with and without) and five planting speeds. Results indicated that increasing planting speed reduced soil moisture and increased soil temperature, adversely affecting soybean nodulation and yield due to uneven plant distribution in the planting furrow. Planting speeds close to 4 km h-1 achieved the best uniformity in plant distribution, nodulation, and soybean yield. Coinoculation enhanced the number and dry mass of nodules and improved soybean grain yield.